2019
DOI: 10.4193/rhin19.178
|View full text |Cite
|
Sign up to set email alerts
|

Minimal unilateral peak nasal inspiratory flow correlates with patient reported nasal obstruction

Abstract: Background: Nasal septoplasty is a common surgical procedure, but a significant number of patients report equal, or some even worsened, symptom load postoperatively. Rhinologists struggle to find objective tests that adequately reflects disease burden. This study aimed to evaluate the correlation between the PNIF measurement of the most obstructed side with patient reported outcomes. Methods: Bilateral and unilateral PNIF measurements were performed before and after topical decongestion in 528 patients schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…This study found a statistically significant but weak correlation between patient‐reported evaluation of nasal breathing and objective measurement of nasal airflow in patients not selected according to symptoms of nasal obstruction or to the level of nasal airflow. This finding is consistent with other studies that evaluated patients with nasal airway obstruction and found a statistically significant but weak correlation between PNIF level and NOSE or VAS score 34‐40 …”
Section: Discussionsupporting
confidence: 92%
“…This study found a statistically significant but weak correlation between patient‐reported evaluation of nasal breathing and objective measurement of nasal airflow in patients not selected according to symptoms of nasal obstruction or to the level of nasal airflow. This finding is consistent with other studies that evaluated patients with nasal airway obstruction and found a statistically significant but weak correlation between PNIF level and NOSE or VAS score 34‐40 …”
Section: Discussionsupporting
confidence: 92%
“…A total 5 out of 8 studies identified a correlation between PNIF and PROMs in AR and CRS. The strength of correlation was weak in the majority of the included papers (0.35 < r < 0.5) 17,42,44,59,60 ; however, stronger correlation was noted in CRS patients ( r > 0.5) 17,50,58 . The only publication in the DNS population found no statistically significant correlation between PNIF and PROMs, post‐septorhinoplasty.…”
Section: Resultsmentioning
confidence: 95%
“…For nasal obstruction, the most commonly studied PROM was the visual analogue scale (VAS) for nasal obstruction which was used in 45% of the included studies 17,36,40,41,44,48–50,52–60 . Only 25% of the included papers used the validated NOSE questionnaire for nasal obstruction 30,31,35,46,48,50,61,62 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations